2017
DOI: 10.1002/rcm.7945
|View full text |Cite
|
Sign up to set email alerts
|

Negative ions, molecular electron affinity and orbital structure of cata‐condensed polycyclic aromatic hydrocarbons

Abstract: The obtained results contribute to the field of electron-molecule interactions and may be of importance for the better comprehension of the functioning of organic electronics, for the synthesis of relevant novel materials, and the development of efficient analytical methods capable of discriminating structural isomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 92 publications
(145 reference statements)
0
16
0
Order By: Relevance
“…One of the major criticisms of the ECD method is that the products of the reaction are not identified. However, the lifetimes reported in both studies by Khatymov et al support the assumption that the products in the ECD are the molecular negative ions of these molecules. In addition, the recent determination of the electron affinity of phenanthrene by photon studies demonstrates that its electron affinity is positive .…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…One of the major criticisms of the ECD method is that the products of the reaction are not identified. However, the lifetimes reported in both studies by Khatymov et al support the assumption that the products in the ECD are the molecular negative ions of these molecules. In addition, the recent determination of the electron affinity of phenanthrene by photon studies demonstrates that its electron affinity is positive .…”
Section: Resultsmentioning
confidence: 66%
“…Table shows the ground state AE a for the AHC considered herein, the ionization energies from the NIST database and the lifetimes from the subject article and Khatymov et al There are reported photon AE a values for anthracene, 0.530 (8) eV; pyrene, 0.41 (1) eV; and chrysene, 0.32 (1) eV, in the NIST database . Not in the database, however, is the photon AE a value for phenanthrene of 0.12 eV .…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations